Effects of Ti, PMMA, UHMWPE, and Co-Cr wear particles on differentiation and functions of bone marrow stromal cells - Jiang, Yunpeng (2013)
The current study investigates the roles of orthopaedic biomaterial particles (Ti, PMMA, UHMWPE, Co-Cr) on the differentiation and functions of bone marrow stromal cells (BMSCs). Cells were isolated from femurs of BALB/c mice and cultured in complete osteoblast-induction medium in presence of micron-sized biomaterial particles at various doses. MTT assay and lactate dehydrogenase (LDH) assay were performed for cell proliferation and cytotoxicity. Differentiation and function of osteoblasts were evaluated by alkaline phosphatase (ALP), osteocalcin, RANKL, OSX, and Runx2 expressions. Murine IL-1, IL-6 and TNFα in culture media were determined by ELISA. Challenge with low doses of Ti, UHMWPE, or Co-Cr particles markedly promoted the bone marrow cell proliferation while high dose of Co-Cr significantly inhibited cell growth (p<0.05). Cells challenged with low dose of PMMA or UHMWPE particles (0.63 mg/ml) exhibited strong ALP activity, whereas Ti, and Co-Cr groups showed minimal effects (p<0.05). UHMWPE and Ti particles also promoted higher expression of pro-inflammatory cytokines. Real-time PCR data suggested that cells treated with low dose (0.5mg/ml) particles resulted in distinctly diminished RANKL expression compared to those exposed to high concentrated (3mg/ml) particles. In conclusion, various types of wear debris particles behaved differently in the differentiation, maturation, and functions of osteogenic cells; and the particulate debris-interacted bone marrow stromal cells may play an important role in the pathogenesis and process of the debris-associated aseptic prosthetic loosening.